Effect of Webinar Multimedia Platform on Students’ Academic Performance in Selected Educational Technology Concepts in University of Ilorin - Nuhu, Kehinde Muritala; Onojah, Amos Ochayi (Indonesian Journal of Multidiciplinary Research, 2022)
The study investigated the effect of Webinar Multimedia Platform in selected Educational Technology Concept on Students’ Academic Performance in the University of Ilorin. A descriptive study design was adopted for the measurement of respondent’s opinions on the issue related to webinar multimedia tools and students’ academic performance. The study population constitutes 50 students in the Educational Technology Department at the University of Ilorin considering t-test statistical tools. The findings of the study revealed that (i) There was no significant difference between the performance of undergraduates taught selected educational technology concepts using Webinar and those that were taught with the conventional lecture method in favor of the experimental group; (ii) There was no significant difference in the mean score’s performance of male, and (iii) female students that were exposed to Webinar, (iv)           The students that were exposed to Webinar had positive reactions toward the use of Webinar, and (v) There was no significant difference between male and female students’ reactions towards the use of Webinar. The study concluded that Webinar was used and found effective for learning the selected Educational Technology concepts. The two hypotheses that were tested were retained. Based on the findings, the researcher recommends that Webinar is a very effective supplementary tool that will enhance students’ academic performance.